Clinical application of "Double R" anastomosis technique in laparoscopic pancreaticoduodenectomy procedure. Issue 21 (28th May 2021) - Tang, Wei; Qiu, Jian-Guo; Li, Gui-Zhong; Zhao, Yu-Fei; Du, Cheng-You
Abstract : Abstract: Laparoscopic pancreaticoduodenectomy (LPD) is widely used as a treatment for periampullary tumors and pancreatic head tumors. However, postoperative pancreatic fistula (POPF), which significantly affects mortality and length of hospital stay of patients, remains one of the most common and serious complications following LPD. Though numerous technical modifications for pancreaticojejunostomy (PJ) have been proposed, POPF is still the "Achilles heel" of LPD. To reduce POPF rate and other postoperative complications following LPD by exploring the best approach to manage with the pancreatic remnant, a novel duct-to-mucosa anastomosis technique named Double Layer Running Suture (Double R) for the PJ was established. During 2018 and 2020, a totally 35 patients who underwent LPD with Double R were included, data on the total operative time, PJ duration, estimated blood loss, recovery of bowel function, postoperative complications, and length of hospital stay were collected and analyzed. The average duration of surgery was (380 ± 69) minutes. The mean time for performing PJ was (34 ± 5) minutes. The average estimated blood loss was (180 ± 155) mL. The overall POPF rate was 8.6% (3/35), including 8.6% (3/35) for the biochemical leak, 0% (0/35) for Grade B, and 0% (0/35) for Grade C. No patient suffered from biliary fistula, post-pancreatectomy hemorrhage, and intra-abdominal infection, the 30-day mortality was 0%. Double R anastomosis is potentially a safe, reliable, and rapid anastomosis with a low rate of POPF and post-pancreatectomy hemorrhage. It provides surgeons more options when performing LPD. However, its safety and effectiveness should be verified further by a larger prospective multicenter study.